A New Probability Distribution for Modeling Failure and Service Times: Properties, Copulas and Various Estimation Methods - Elgohari, Hanaa; Ibrahim, Mohamed; M. Yousof, Haitham (Statistics, Optimization & Information Computing, 2021)
In this paper, a new generalization of the Pareto type II model is introduced and studied. The new density can be “right skewed” with heavy tail shape and its corresponding failure rate can be “J-shape”, “decreasing” and “upside down (or increasing-constant-decreasing)”. The new model may be used as an “under-dispersed” and “over-dispersed” model. Bayesian and non-Bayesian estimation methods are considered. We assessed the performance of all methods via simulation study. Bayesian and non-Bayesian estimation methods are compared in modeling real data via two applications. In modeling real data, the maximum likelihood method is the best estimation method. So, we used it in comparing competitive models. Before using the the maximum likelihood method, we performed simulation experiments to assess the finite sample behavior of it using the biases and mean squared errors.